The value of IgG to IgM ratio in predicting secondary dengue infection - I Putu Gede Karyana; Hendra Santoso; Bagus Ngurah Putu Arhana (Indonesian Pediatric Society Publishing House, 2016)
Background The determination of primary or secondary dengue infection using hemagglutination inhibition (HI) test is time-con- suming. The IgG to IgM ratio which can be obtained earlier was used by several studies to differentiate secondary from primary infection, but they still reported various cut-off points. Objective To find the diagnostic value and best cut off point of IgG to IgM ratio for predicting secondary dengue infection. Methods This was a prospective study carried out between July 2003 and June 2004. Children with suspected dengue hemor- rhagic fever (DHF) were tested for HI during acute and convales- cent phase. The IgG and IgM titer were examined during the acute phase using ELISA method. Results Sixty-two children were recruited, 48 with secondary in- fection and 14 with primary infection. The prevalence of second- ary infection was 77%. The best cut off point of the IgG to IgM ratio to predict secondary infection was >1.1 with sensitivity of 87.5%, specificity 92.9%, likelihood ratio 12.3, and post test probability 97.7%. Conclusion The IgG to IgM ratio of >1.1 is a good predictor for secondary infection